Optimization and activation of renewable durian husk For biosorption of Pb(ii) from wastewater - Ngabura, Mohammed; Hussain, Siti Aslina; Ghani, Wan Abdul Karim; Jami, Mohammed Saedi; Tan, Yen Ping (2018)
Biosorption of Lead Pb(II) on durian husk activated carbon (DHAC) was investigated in this study. The effects of operating variables such as pH, biosorbent dose, temperature, initial metal ion concentration and contact time were studied using response surface methodology (RSM). The experimentation was performed in two sets, namely; set 1 and set 2. For experimental set 1, pH was optimized (pH = 7) and the optimum conditions for the remaining parameters were determined as 0.39 DHAC dose, 60 min contact time and 100 mg/L of initial metal ion concentration, yielded maximum biosorption capacity of 14.6 mg/g. Pertaining to experimental set 2, 41.27 °C, 8.95 and 99.96 mg/L were the ascertained optimum conditions for temperature, pH and initial Pb(II) concentration, respectively; which revealed maximum adsorption capacity of 9.67 mg/g. Fourier transform infrared (FTIR) analysis was performed to quantify the major functional groups present on the surface of DHAC that are active in the sorption of Pb(II). The equilibrium adsorption data obeyed Langmuir isotherm and pseudo-second-order kinetic models with maximum Langmuir uptake of 36.1 mg/g. The abundant durian husk could be utilized effectively for removal Pb(II) from polluted water.